Coexistence of resistance to thyroid hormone and ectopic thyroid: ten-year follow-up - Guo,Man-Li (2016)
SUMMARY Resistance to thyroid hormone (RTH) coexisting with ectopic thyroid is rare. Here we report a case of RTH with ectopic thyroid. A ten-year-old girl had been misdiagnosed as congenital hypothyroidism and treated with levothyroxine since she was born. Ten-year follow-up showed that the elevated thyrotropin was never suppressed by levothyroxine and no signs indicating hyperthyroidism or hypothyroidism despite elevated FT3 and FT4 levels. Therefore the girl developed no defects in physical and cognitive development. Pituitary adenoma was excluded by magnetic resonance imaging. Ultrasonography did not find the thyroid gland in the normal place, while the thyroid scan found a large lingual thyroid gland. The octreotide inhibition test showed a reduction in thyrotropin by 41.98%. No mutation was detected in the thyroid hormone receptor (THR) β, THRα, thyrotropin receptor (TSHR), and GNAS1 genes. To our knowledge, it is an interesting RTH case coexisting with lingual thyroid.